(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Several professors from the School of Industrial Engineering (Eii) of the University of Valladolid (UVa) designed the Eii Tutorial Mentor Care Program (PAT_Mentor) in the 15-16 academic year (implemented from the 16-17 academic year to the present). It has always been under the umbrella of the Teaching Innovation Projects convened by the UVa and since the 21-22 academic year it has constituted one of the Teaching Innovation Groups (GID) of the UVa, which highlights the importance of consolidating the Teaching Innovation Programs Help and Guidance at the University. This work shows the trajectory followed until the constitution of the GID.